Emotional Regulation in Adolescent Girls when Experiencing Menstrual Pain or Dysmenorrhea - Lestari Lestari; Dyah Siti Septiningsih (Proceedings Series on Social Sciences & Humanities, 2021)
The biological pride of young women is characterized by a standard physical mechanism of menstruation or menstruation followed by pain in the lower abdomen. The pain results in psychological symptoms such as anxiety, tension, anger, or emotion. Young women who cannot regulate their feelings properly are more likely to experience severe pain or so-called dysmenorrhea. Emotional regulation is the achievement of emotional balance performed by a person either from his attitude or behavior. This study aims to examine the regulation of emotions in young women who experience dysmenorrhea during menstruation. Assessment through aspects of emotional regulation, namely emotional regulation strategies, behaviors to achieve goals, control emotional responses, and acceptance of emotional responses. This research uses qualitative research methods with a case study approach. Data retrieval was conducted through semi-structured interviews of two primary informants and four secondary informants. Credibility using triangulation of sources and methods. Data analysis using interactive model data analysis. This study's findings are that both young women's ability to regulate their emotions during menstruation can relieve severe pain or dysmenorrhea during menstruation.